1991
DOI: 10.1093/ije/20.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cases of Myocardial Infarction: Hospital Discharge Data and Mortality Data Compared to Myocardial Infarction Community Registers

Abstract: Identification of incident myocardial infarction (MI) cases in a defined population using hospital discharge data and mortality data in combination has been suggested. This method of case identification was compared to that of use of MI community registers set up in accordance with principles adopted in a World Health Organization collaborative programme. The comparison comprised data for four Swedish cities over a number of years. On average 81% of incident hospital-treated cases below 65 years of age identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…All AMI events that occur 28 days after the date of admission are treated as new events. More detailed information regarding the register is presented elsewhere (Hammar et al, 1991).…”
Section: The Swedish National Acute Myocardial Infarction Registermentioning
confidence: 99%
“…All AMI events that occur 28 days after the date of admission are treated as new events. More detailed information regarding the register is presented elsewhere (Hammar et al, 1991).…”
Section: The Swedish National Acute Myocardial Infarction Registermentioning
confidence: 99%
“…Therefore, several studies have investigated the validity of data about CHD or acute myocardial infarction in national registers by comparing them with specific study registers [8][9][10][11][12][13][14][15]. These studies showed a wide range in the estimated values for the validity of the data in national registers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the confidence intervals were reasonably narrow, and a true excess risk greater than about 30% seems very unlikely. The method of identifying cases has been evaluated previously and found to have a high agreement with established diagnostic criteria for myocardial infarction (17)(18)(19). Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of all men 40 to 69 years of age residing in Stockholm County during the period 1976-1996. We identified incident cases of acute myocardial infarction in the study population by using registers of hospital discharges and deaths (17)(18)(19). The method of case ascertainment has been validated and found to have a high sensitivity for identifying new cases of myocardial infarction in a defined population and also a high positive predictive value for Sweden (20) and Stockholm County (19).…”
Section: Study Population and Methodsmentioning
confidence: 99%